I think (that) something’s missing: Complementizer deletion in nonnative e-mails - Durham, Mercedes (Zakład Filologii Angielskiej: Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2011)
Sociolinguistic competence is not often examined in nonnative English acquisition. This is particularly true for features where the variants are neither stylistically nor socially constrained, but rather are acceptable in all circumstances. Learning to use a language fully, however, implies being able to deal with this type of ‘difficulty,’ and understanding what type of variable features nonnative speakers acquire with ease and which ones they do not may help us better understand more general processes of second language acquisition. By comparing the rates of complementizer deletion of nonnative to native speakers and examining their distributions across various internal and external factors, this paper addresses these issues and offers an example of acquisition of what is, in some ways, an invisible variant. Furthermore, by focusing on a Swiss student association, the paper is also able to compare the patterns of French, German and Italian native speakers, to examine to what extent they differ in English.
Keywords: sociolinguistic competence; complementation; complementizer deletion; zero complementizer